ULTRASTRUCTURE OF THE OLFACTORY ORGAN IN THE STRIPED SNAKEHEAD OPHIOCEPHALUS STRIATUS (BLOCH). - S.C. MASRAM; V.V. BAILE (International Journal of Pharma and Bio Sciences, 2014)
Olfactory organ of Ophiocephalus striatus Bloch consists of quadrangular shaped olfactory rosette, long olfactory nerve and sessile olfactory bulb. Olfactory rosette comprises of elongated olfactory lamellae arranged in rostro-caudal direction. In olfactory lamellae, sensory epithelium consists of olfactory receptor cells, supporting cells, basal cells and goblet cells. Olfactory receptor cells are of two types microvillous and ciliated. Cells of olfactory bulb are organized in four concentric layers. Outer layer is olfactory nerve layer formed byaxons of olfactory receptor cells. Inner to it is glomerular layer where axons of olfactory receptor cells synapse with dendrites of mitral cells. Next towards deeper part is mitral cell layer which comprises larger multipolar mitral cells. Central core is formed by granular cell layer with small granular cells.